2007
DOI: 10.1016/j.bbrc.2007.08.166
|View full text |Cite
|
Sign up to set email alerts
|

Potent inhibition of tau fibrillization with a multivalent ligand

Abstract: Small-molecule inhibitors of tau fibrillization are under investigation as tools for interrogating the tau aggregation pathway and as potential therapeutic agents for Alzheimer's disease. Established inhibitors include thiacarbocyanine dyes, which can inhibit recombinant tau fibrillization in the presence of anionic surfactant aggregation inducers. In an effort to increase inhibitory potency, a cyclic bis-thiacarbocyanine molecule containing two thiacarbocyanine moieties was synthesized and characterized with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 22 publications
(35 reference statements)
2
17
0
1
Order By: Relevance
“…Although compound 16 can form H-aggregates or a closed clamshell conformation, the four-fold improvement in activity was correlated to the open monomeric form, indicating that the improvement in potency results from the compounds multivalency and not from aggregation. [47] 2.5. Phenothiazines, Porphyrins, and Polyphenols Taniguchi et al [44] reported three classes of compounds active on tau aggregation inhibition on htau46 (htau34 isoform, 412 amino acids, first insert, four repeats) with IC 50 values between 1.2 mm (myrcetin, Figure 14) and 12 mm (thionin).…”
Section: Tau Aggregation Inhibitorsmentioning
confidence: 99%
“…Although compound 16 can form H-aggregates or a closed clamshell conformation, the four-fold improvement in activity was correlated to the open monomeric form, indicating that the improvement in potency results from the compounds multivalency and not from aggregation. [47] 2.5. Phenothiazines, Porphyrins, and Polyphenols Taniguchi et al [44] reported three classes of compounds active on tau aggregation inhibition on htau46 (htau34 isoform, 412 amino acids, first insert, four repeats) with IC 50 values between 1.2 mm (myrcetin, Figure 14) and 12 mm (thionin).…”
Section: Tau Aggregation Inhibitorsmentioning
confidence: 99%
“…161,162 A multivalent cyane derivative, the cyclic bis-thiacarbocyanine, inhibits tau aggregation in vitro with approximately a fourfold higher potency than the monovalent cyane itself. 163 The mechanism by which multivalent ligands interfere with protein aggregation has been speculated to involve their binding to oligomers, thereby preventing incorporation of new molecules into filaments. 164 Alternatively, these small-molecule inhibitors might decrease the concentration of aggregation-prone proteins by sequestration into protein-inhibitor complexes.…”
Section: Rhodanines and Anthraquinonesmentioning
confidence: 99%
“…A similar biphasic behavior is shown by other cyanines [241,242] in cellular models of tau aggregation characterized by mutant and WT tau isoforms [243]. Multivalent, macrocyclic benzothiazoliumbenzothiazole cyanines connected through their N atoms (e.g., 6.32, Figure 6.11) are stronger tau aggregation inhibitors due to multivalency [244,245]. The most potent macrocycles adopt an "open"/multi-presenting conformation, while "closed" macrocycles are less active.…”
Section: Interfering With (Neuro)toxic Tau Species In the Aggregationmentioning
confidence: 64%